2013
DOI: 10.1002/14651858.cd005481.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Co-formulated abacavir-lamivudine-zidovudine for initial treatment of HIV infection and AIDS

Abstract: Co-formulated abacavir-lamivudine-zidovudine for initial treatment of HIV infection and AIDS (Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 43 publications
(38 reference statements)
0
11
0
Order By: Relevance
“…Based on a search strategy published by Shey et al [ 24 ], we used both text words and medical subject heading (MeSH) terms, for example abacavir, antiretroviral, HIV, acquired immunodeficiency syndrome , child , paediatric , adolescent and randomized controlled trial to form the basis of the search strings. We also used these terms in different combinations and with different spellings, and adapted them as appropriate for each database.…”
Section: Methodsmentioning
confidence: 99%
“…Based on a search strategy published by Shey et al [ 24 ], we used both text words and medical subject heading (MeSH) terms, for example abacavir, antiretroviral, HIV, acquired immunodeficiency syndrome , child , paediatric , adolescent and randomized controlled trial to form the basis of the search strings. We also used these terms in different combinations and with different spellings, and adapted them as appropriate for each database.…”
Section: Methodsmentioning
confidence: 99%
“…There are however systematic reviews on abacavir-containing combination antiretroviral regimens in adults [12,13,16,19]. The study team plans to address this gap with the proposed systematic review outlined in this protocol.…”
Section: Discussionmentioning
confidence: 99%
“…cART only consisting of ABC/3TC/ZDV is generally not recommended as first‐line treatment because of suboptimal virological activity . However, a recent Cochrane review of the use of ABC/3TC/ZDV for initial treatment of HIV infection concluded that this regimen might still be useful, especially in patients with pre‐existing hyperlipidaemia and those not tolerating ritonavir . The combination of ABC/3TC/ZDV is also considered an acceptable alternative by the World Health Organization (WHO) in selected situations where standard cART is contraindicated or unavailable .…”
Section: Discussionmentioning
confidence: 99%